ENCOMS: Argentinian survey in cost of illness and unmet needs in multiple sclerosis - Celica Ysrraelit; Fernando Caceres; Andres Villa; Marcela Parada Marcilla; Jorge Blanche; Marcos Burgos; Ignacio Casas Parera; Oscar Colombo; Ernesto Crespo; Norma Deri; Patricio Labal; Monica Maluendez; et al. (Arquivos de Neuro-Psiquiatria)
The objective of the study was to assess the cost of multiple sclerosis (MS) patients in Argentina categorized by disease severity using a societal perspective. Method: Cross-sectional study including MS patients from 21 MS centers in 12 cities of Argentina. Patients were stratified by disease severity using the expanded disability status scale (EDSS) (group 1 with EDSS score between 0 and 3; group 2 with EDSS >3 and <7; group 3 with EDSS ≥7). Direct and indirect costs were analyzed for the second quarter of 2012 from public sources and converted to US Dollars. Results: 266 patients were included. Mean annual cost per MS patient was USD 36,025 (95%CI 31,985-38,068) for patients with an EDSS between 0-3; USD 40,705 (95%CI 37,199-46,300) for patients with EDSS >3 and <7, and USD 50,712 (95%CI 47,825-62,104) for patients with EDSS ≥7. Conclusions: This is the first Argentine study evaluating the costs of MS considering disease severity.